Selegilina reverte a piora da memória inuzida por Aβ25-35 em camundongos: envolvimento da atividade da MAO-B - Pazini, Andreia Martini (2013)
Alzheimer s disease (AD) is biochemically characterized by the occurrence of extracellular deposits of amyloid beta peptide (Aβ) and intracellular deposits of the hyperphosphorylated tau protein, which are causally related to the pathological hallmarks senile plaques and neurofibrillary tangles. Monoamine oxidase B (MAO-B) activity, an enzyme involved in the oxidation of biogenic monoamines, is particularly high around the senile plaques and increased in AD patients in middle to late clinical stages of the disease. Selegiline, a selective and irreversible MAO-B inhibitor, improves learning and memory in AD patients. Notwithstanding, its mechanism of action is still not completely known. The current study aimed to investigate whether selegiline improves the Aβ25-35 induced cognitive deficit in the object recognition task in mice. In addition, we investigated whether selegiline alters MAO-B and MAO-A activities in the hippocampus, perirhinal and remaining cerebral cortices of Aβ25-35-injected mice. Acute (1 and 10 mg/kg, p.o., immediately post-training) and subchronic (10 mg/kg, p.o., seven days after Aβ25-35 injection and immediately post-training) administration of selegiline reversed the cognitive impairment induced by Aβ25-35 (3 nmol, i.c.v.). Acute administration of selegiline (1 mg/kg, p.o.) in combination with Aβ25-35 (3 nmol) decreased MAO-B activity in the perirhinal and remaining cerebral cortices. Acute administration of selegiline (10 mg/kg, p.o.) decreased MAO-B activity in hippocampus, perirhinal and remaining cerebral cortices, regardless of Aβ25-35 or Aβ35-25 treatment. MAO-A activity was not altered by selegiline or Aβ25-35. In summary, the current findings further support a role for MAO-B in the cognitive deficits observed in AD.